Antibacterial, antibiofilm and cytotoxic effects of Nigella sativa essential oil coated gold nanoparticles. (February 2016) - Manju, Sivalingam; Malaikozhundan, Balasubramanian; Vijayakumar, Sekar; Shanthi, Sathappan; Jaishabanu, Ameeramja; Ekambaram, Perumal; Vaseeharan, Baskaralingam
Abstract: This study reports the biological synthesis of gold nanoparticles using essential oil of Nigella sativa ( Ns EO-AuNPs). The synthesized Ns EO-AuNPs were characterized by UV–visible spectra, X-ray diffraction (XRD), FTIR and Transmission electron microscopy (TEM). UV–vis spectra of Ns EO-AuNPs showed strong absorption peak at 540 nm. The X-ray diffraction analysis revealed crystalline nature of nanoparticle with distinctive facets (111, 200, 220 and 311 planes) of Ns EO-AuNPs. The FTIR spectra recorded peaks at 3388, 2842, 1685, 1607, 1391 and 1018 cm −1 . TEM studies showed the spherical shape of nanoparticles and the particle size ranges between 15.6 and 28.4 nm. The antibacterial activity of Ns EO-AuNPs was greater against Gram positive Staphylococcus aureus MTCC 9542 (16 mm) than Gram negative Vibrio harveyi MTCC 7771 (5 mm) at the concentration of 10 μg ml −1 . Ns EO-AuNPs effectively inhibited the biofilm formation of S . aureus and V . harveyi by decreasing the hydrophobicity index (78% and 46% respectively). The in - vitro anti-lung cancer activity confirmed by MTT assay on the cell line of A549 carcinoma cells showed IC50 values of bulk Au at 87.2 μg ml −1, N . sativa essential oil at 64.15 μg ml −1 and Ns EO-AuNPs at 28.37 μg ml −1 . The IC50 value showed that Ns EO-AuNPs was highly effective in inhibiting the A549 lung cancer cells compared to bulk Au and N . sativa essential oil. Graphical abstract: Highlights: Essential oil of Nigella sativa based gold nanoparticles ( Ns EO-AuNPs) was synthesized. Ns EO-AuNPs was characterized by UV–Vis spectrophotometer, XRD, FTIR, TEM and EDAX. Antibacterial and antibiofilm activity of Ns EO-AuNPs was assessed against S . aureus and V . harveyi . Cytotoxicity of Ns EO-AuNPs was tested on human lung cancer A549 cells. Ns EO-AuNPs effectively inhibited the growth of A549 lung cancer cells.